The Political Economy of National Security, Critical Infrastructure and Securitization of Foreign Investments
XVIII, 270 p. 8 illus., 1 illus. in color.
Keywords: “Morten Skumsrud Andersen and Jakub M. Godzimirski have delivered the academic and policy communities quite the favour in steering this fine collection of the political economy of national security and critical infrastructure. The collection includes a range of national cases—China, Finland, The Netherlands, Russia, UK and US—that provide both an overview and avenue for comparison, as well as a European approach. Theoretically they innovate by dusting off and revising assumed relationships between economic interdependence and great power rivalry, showing how new forms of securitization need to be considered.” --Leonard Seabrooke, Professor of International Political Economy and Economic Sociology, Copenhagen Business School, Denmark This book examines how new flows of foreign direct investments from autocracies are framed, their effects, and the policy responses to them, within the context of challenges to the international liberal order. Chapters address thematic and regional issues, from national investment controls and threat perceptions to China and Russia’s responses. Collectively, they explore a new dynamic in international politics: the securitization of money crossing borders. Historically, foreign investments operated under minimal global regulation, based on the assumption that they were beneficial, and profit driven. However, the past decade has witnessed a radical shift in approaches to foreign investments due to changing investment patterns and the entry of state-sponsored actors into this traditionally unregulated realm. China and Russia are seen to leverage foreign investments to advance their long-term economic and political objectives. The book comprehensively examines the subsequent repositioning of foreign investment policy and its consequences for national and international politics. Jakub M. Godzimirski is Research Professor, Research group on Russia, Asia and International Trade, Norwegian Institute of International Affairs (NUPI), Oslo, Norway. Morten Skumsrud Andersen is Senior Research Fellow at the Norwegian Institute of International Affairs (NUPI), head of its research group on Global Order and Diplomacy, and the PI of the research project “Consequences of Investments for National Security” (COINS).